Legal justification for the prevention of corruption risks associated with the participation of state civil servants in the management of commercial organizations - S. G. Eremin (Управленческие науки)
The purpose of the article is to investigate the problem of preventing corruption risks associated with the participation of state civil servants on a gratuitous basis in the management of organizations and enterprises of various forms of ownership.The objectives of the article are to study the cases of participation of persons holding public positions in the management of a commercial or non-profit organization allowed by the legislator. To consider the external and internal corruption risks associated with the participation of state civil servants on a gratuitous basis in the management of organizations and enterprises of various forms of ownership, to clarify the causes of their occurrence.The practical result of the study is that, based on the provisions of Russian and international legal acts, in particular ISO 26000, ISO 37000, ISO 37001 and ISO 37002 standards, a list of measures and conditions for preventing corruption risks associated with the participation of state civil servants on a gratuitous basis in the management of organizations and enterprises of various forms of ownership has been developed.